2021
DOI: 10.1186/s12905-021-01412-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of attitudes towards conditions to provide safe abortion among new medical graduates in Thailand, 2018: an application of cross-sectional survey with factor analysis

Abstract: Background Unsafe abortion is one of the major public health problems in Thailand. Although the penal code of Thailand and the Thai Medical Council permit doctors to perform safe abortion in certain conditions, little is known about the attitudes that new medical doctors have towards abortion. The objectives of this article are to explore the attitudes towards abortion in certain conditions among new medical graduates and to identify factors related to those attitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The majority of participants agreed that a serious fetal defect warranted abortion, while the least priority was given to socioeconomic problems as a reason for providing abortion services. Our results were consistent with those of a study by Saengruang et al [35], which showed that most new medical graduates in Thailand agreed to perform abortions based on health conditions of the mother and fetus and not socioeconomic problems. This may be because making decisions to provide abortion services in cases where the fetus is nonviable or the mother's health/ life is under threat is uncomplicated.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of participants agreed that a serious fetal defect warranted abortion, while the least priority was given to socioeconomic problems as a reason for providing abortion services. Our results were consistent with those of a study by Saengruang et al [35], which showed that most new medical graduates in Thailand agreed to perform abortions based on health conditions of the mother and fetus and not socioeconomic problems. This may be because making decisions to provide abortion services in cases where the fetus is nonviable or the mother's health/ life is under threat is uncomplicated.…”
Section: Discussionsupporting
confidence: 93%
“…A study by Daniel et al, revealed that female gynecologists and medical students declared readiness to assist in abortion more commonly than men if the dispensing requirements for mifepristone were removed [25]. A study conducted in the graduates of medical schools showed that men were more commonly willing to perform terminations personally in cases of social indications [22]. Analogous results were obtained in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…In the USA, it is legal for family doctors to prescribe abortion pills. A study conducted in the students of medicine in Thailand revealed that the majority of students declared they were willing to perform an abortion in case of a threat to maternal or fetal life, or if the pregnancy was a result of rape [22]. A small group declared that they were ready to perform a termination without medical indications.…”
Section: Discussionmentioning
confidence: 99%
“…This presents an opportunity to fortify future curricula to emphasize decriminalized circumstances for abortions. Other studies 13,15 on healthcare providers in Thailand also showed that knowledge of abortion law was not ideal; however, most healthcare providers are receptive to acquiring knowledge of abortion care regardless of their stance on the practice. 16,17 Our study found that better knowledge of abortion legislation was associated with a positive attitude toward abortion practice.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 Practitioners felt more supportive of safe abortion practices and were more inclined to provide such services after acquisition of training. 15 Participation of nurses in abortion care is one of the many barriers in provision of abortion care 19 ; this finding is reassuring as it offers an opportunity to mitigate the stigma associated with abortion care. 11 Religion played an important role in attitudes toward abortion, both in our study and in previous studies.…”
Section: Discussionmentioning
confidence: 99%